2005
DOI: 10.1080/03650340500077836
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a transformation scale between bioindicatively determined water supply levels of grassland sites and mean moisture indicator values according to Ellenberg

Abstract: Data on the moisture level of grassland sites have traditionally been based on the water supply levels according to Petersen (1952) in east German relevant technical literature. The question was to what extent these data are comparable to Ellenberg's widely-known moisture indicator values. The transformation scale for water supply levels and moisture values suggested in this paper was based on more than 500 grassland relevés collected in the German federal states of Brandenburg and Mecklenburg-Western Pomerani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It is well known that forest species are highly correlated with environmental factors (Böcker et al 1983;Kaiser and Käding 2005;Schaffers and Sykora 2000;Southall et al 2004;Schmidtlein and Ewald 2003). The challenge in plant ecology is to select a reduced set among the innumerable factors that are implied in the response of species and communities.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that forest species are highly correlated with environmental factors (Böcker et al 1983;Kaiser and Käding 2005;Schaffers and Sykora 2000;Southall et al 2004;Schmidtlein and Ewald 2003). The challenge in plant ecology is to select a reduced set among the innumerable factors that are implied in the response of species and communities.…”
Section: Introductionmentioning
confidence: 99%
“…EIVs summarize in scales with nine degrees (up to twelve for soil moisture indicator) the large amount of ecological information on plants and plant communities associated with environmental measurements of edaphic and climatic parameters. Limitation and strengths of the Ellenberg's approach have been long debated (e.g., Ewald 2003), though a number of studies showed a good agreement between indicators and environmental variables (e.g., Fanelli et al 2007, Schaffers & Sykora 2000, Schmidtlein & Ewald 2003, Southall et al 2003, Kaiser & Käding 2005. EIVs represent a first model of bioindication applied for the first time to the flora of Germany (Ellenberg 1974), and then extended to Netherlands (van der Maarel et al 1985), Norway (Vevle & Aase 1980), Sweden (Diekmann 1995), Estonia (Pärtel et al 1996(Pärtel et al , 1999, Poland (Roo-Zieliska & Solon 1988), Great Britain (Hawkes et al 1997), northeastern France (Thimonier et al 1994) and Italy (Celesti Grapow et al 1993, Pignatti 2005, Fanelli et al 2006b.…”
Section: Introductionmentioning
confidence: 99%